The study of in Vitro Interaction of Ciprofloxacin with Paracetamol and Zinc in Aqueous Medium (Journal of Scientific Research, 2012)
Concurrent administration of more than one drug is a common practice in medical science and in such case one drug may affect the pharmacology of another drug. Ciprofloxacin is a commonly used antibiotic in Bangladesh and frequently prescribed with paracetamol and zinc salt for concomitant use in patients suffering from infections. Therefore, the interaction of ciprofloxacin with paracetamol and zinc salt was studied in vitro at pH 1.2, 6.8 and 7.4 which are related to gastric, intestinal juices and blood, respectively. Analysis of drug-drug and drug-metal complexation was carried out by using UV/VIS spectrophotometer as well as the conductometric titration. It was observed that ciprofloxacin formed complex with paracetamol and zinc at pH 1.2.© 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v4i3.8709 J. Sci. Res. 4 (3), 701-708 (2012)